Criteria and computer-aided design of solid slab to BS 8110 - the structural use of concrete - Che Muda, Zakaria (1988)
Criteria for the limit state design of reinforced concrete slabs are discussed. A step by step longhand solution for some of rectangular slabs is given in order to explain the limit state concept of BS 8110. A general purpose computer program written in GWBASIC calculates the ultimate moments, reinforcement area, spacing, deflection, and local damage and crack widths in any specific direction.